What Students Learn from Early Field Experiences A Case Study - Goodman, Jesse ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A study was made of an early field practicum, in elementary education, which theoretically emphasized quantity and diversity in the students' field experiences and allowed them the opportunity to apply newly acquired curriculum methods and theories. Ten student teachers were intensively interviewed and observed over a six month period. It was apparent that the approved curriculum was rigidly followed. Content and procedures were predetermined according to standard materials. In most cases, students drilled and/or tested pupils' competency of prespecified short term facts and/or skills. Most had little involvement in curriculum development or decision making. The impression received was that they were being trained as educational technicians. It is suggested that preparation programs should focus on teaching prospective teachers the craft of developing curricula based upon progressive principles of curriculum design. This craft includes choosing topics of study; developing the themes, concepts, or content that make up the topic; researching these themes; discovering resources that children can use to explore the themes; developing activities that illuminate the themes of the topic and promote curiosity, creativity, and thoughtfulness among the pupils; and organizing the themes, resources, and activities into a coherent unit of study. (JD)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 23-27, 1984).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Elementary School Curriculum; Experiential Learning; Field Experience Programs; Higher Education; Practicums; Preservice Teacher Education; Standardized Tests; Student Teacher Relationship; Teacher Role; Teaching Experience; Teaching Methods; Validated Programs; Speeches/Meeting Papers; Reports, Research